The abstract subject of the climate migrant: Displaced by the rising tides of the green energy economy - Scott, D.N. (Dayna Nadine); Smith, A.A. (Adrian A.) (Journal of Human Rights and the Environment, 2017)
A controversial proposal to build themammoth 'Site C' damon the Peace River in northwestern Canada offers an opportunity to explore the intersections of climate and migration issues und